2014
DOI: 10.1007/s40618-014-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and duration of diabetes as risk factors for abnormal lipids: a cross sectional survey of 19,757 patients with type 2 diabetes in China

Abstract: Hyperglycemia defined as HbA1c ≥7.0 % increased risk of high LDL cholesterol in T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…However, the prevalence of low HDL-C increased at first and then declined along with increasing HbA1c, with the lowest prevalence being observed among the 11%≤HbA1c<13% group. A similar trend of lipid distribution was found in the China lipid study, with highest prevalence of low HDL-C among the HbA1c 8% group [11].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the prevalence of low HDL-C increased at first and then declined along with increasing HbA1c, with the lowest prevalence being observed among the 11%≤HbA1c<13% group. A similar trend of lipid distribution was found in the China lipid study, with highest prevalence of low HDL-C among the HbA1c 8% group [11].…”
Section: Discussionsupporting
confidence: 81%
“…Dyslipidemia interacts with glucose metabolism. One previous study have reported that HbA1c was associated with low HDL cholesterol in a J-shaped manner, and hyperglycemia defined as HbA1c≥7.0 % increased risk of high LDL cholesterol in T2DM [11]. Although compared with HbA1c<7% ,T2DM patients with HbA1c≥7% had significantly higher levels of lipid profile [12,13], it is unknown whether there was a linear and significant increase levels of lipid profile associated with HbA1c value of ≥7%.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prevalence of low HDL-C increased at rst and then declined along with advancing HbA1c, with the lowest prevalence being observed among the 11%≤HbA1c<13% group. A similar trend of lipid distribution was found in the China lipid study, with highest prevalence of low HDL-C among the HbA1c 8% group [11].…”
Section: Discussionsupporting
confidence: 81%
“…Although the associations between hyperlipidemia and hyperglycemia were extensively covered in observational studies 911 , the causal relationship for them is still indeterminate. A recent MR-analysis taking common 10 TG-associated SNPs as IV did not support the causal role of TG for increased fasting glucose 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Among which, the elevated TG 46 and LDL-C 7,8 have been affirmatively proved as causal factors for coronary heart disease (CHD). On the other hand, HbA1c was extensively reported to be associated with the circulating lipid profile 911 . Lately, a trajectory analysis on youths with type 1 diabetes demonstrated that elevation of HbA1c from childhood into young adulthood may result in increases in LDL and non-HDL cholesterols 12 .…”
Section: Introductionmentioning
confidence: 99%